Farmers Participation in Applying Silvopasture Technology for Organic Fertilizer Production as A Sustainable Agriculture - Sumarmi Sumarmi; Heni Masruroh; Syamsul Bachri; Agung Suprianto (Geosfera Indonesia, 2023)
Medowo Village is a potential location for plantings due to its location on the slopes of Mount Anjasmoro in Kandangan District, Kediri Regency. Moreover, Medowo Village is renowned for its dairy for cows and goats. This research aimed to determine the type and level of participation in the production of organic fertilizers to support in sustainable agriculture. This research used a qualitative approach and descriptive method. The data was collected through in-depth interviews, participatory observation, and documenting. The identification of key informant was using the purposeful snowball throwing technique. Data analysis used reduction, display, and verification, as well as data validation through Focus Group Discussion (FGD). The discussion was conducted with 20 farmers, with the main topics related to: a) the problem of fertilizer needs in Medowo Village, and b) producing fertilizer for sustainable farming using the Shivansh fertilizer method. According to the results, there were four stages of farmer participation: 1) planning, 2) implementation, 3) utilization of results, and 4) evaluation. The findings indicated that the level of farmer participation is classified as "good" for all stages. Participation is demonstrated specifically by attendance, participation, and enthusiasm. High participation is found mostly in stages that include activities in producing the . Therefore, inviting farmers at the planning stage is essential to increase participation in program.